Nucleic Acid Polymers with Accelerated Plasma and Tissue Clearance for Chronic Hepatitis B Therapy - Ingo Roehl; Stephan Seiffert; Celia Brikh; Jonathan Quinet; Catherine Jamard; Nadine Dorfler; Jennifer A. Lockridge; Lucyna Cova; Andrew Vaillant (Elsevier, 2017)
REP 2139 is a nucleic acid polymer (NAP) currently under clinical development for chronic hepatitis B (HBV) therapy. This preclinical study investigated different REP 2139 analogs that would display reduced accumulation in the serum and tissues, while retaining an antiviral effect against HBV infection. REP 2139 analogs were evaluated in human plasma, CD-1 mice, cynomolgus monkeys, and Pekin ducks. Discrete ribose transformation to 2'OH in selected riboadenosines resulted in a slow degradation in acidified human plasma that plateaued after 48 hr. REP 2165, a REP 2139 analog containing three unmodified riboadenosines equally spaced throughout the polymer, showed similar plasma clearance and tissue distribution as REP 2139 in mice and cynomolgus monkeys after a single dose. Interestingly, after repeated administration, accumulation of REP 2165 in plasma and organs was reduced, indicating a dramatically faster rate of clearance from organs after therapy was ended in both species. Both REP 2139 and REP 2165 were well tolerated at clinically relevant doses, with no alterations in liver, kidney, or hematological function. In chronic duck HBV (DHBV) infection, REP 2165 displayed significantly reduced liver accumulation after repeated dosing but retained antiviral activity similar to REP 2139. These results indicate the therapeutic potential of REP 2165 against chronic HBV infection in patients is similar to REP 2139, but with significantly reduced drug accumulation and improved tissue clearance. Keywords: nucleic acid polymer, HBV, pharmacokinetics